Comportamento de três cultivares de mamona a cinco níveis de irrigação por gotejamento em Pentecoste, CE - Freitas, Cley Anderson Silva De (2009)
The use of the irrigation in cultivars improved has a tendency to favor the increase of the productivity of castor in the semi-arid. This work was carried out in Fazenda Experimental Vale do Curu, Pentecoste, Ceará, Brazil and the objective of the present study was to evaluate the productive characteristics of three castor cultivars of high agricultural importance (IAC Guarani, Mirante 10 e BRS Paraguaçu) under different levels of irrigation. The experimental delineation used was of the blocks at random with subdivided parcels, composed of five treatments in the parcels, with three cultivars in the sub parcels and three repetitions. The treatments was constituted in five levels of irrigation based on the evaporation of the tank Class “A” ECA (T1 = 0,25 ECA; T2 = 0,50 ECA; T3 = 0,75 ECA; T4 = 1,00 ECA; T5 = 1,25 ECA). The result, found a significant effect between cultivars. The variables length and number of fruits per racemes were higher for the IAC Guarani, while the tenor of oil and number of racemes per plant were higher for the Mirante 10. However the Paraguaçu BRS stood out of the rest of cultivars as for the mass of the raceme, mass of the fruits, mass of hundred seeds and productive potential. There was no significant effect of variable tenor of oil with the blades of irrigation. The Mirante 10 presented the largest tenor of oil (40,64 %), with the maximum blade used of 913,4 mm. The best efficiency of the use of the water was obtained by the treatment T5 (913,4 mm) in the BRS Paraguaçu, what turned the productivity of 2872,42 Kg ha -1. The secondary racemes were that more contributed with the total productivity.